Exploring NNests Instructional Competency in Teaching Writing Skills for Middle School Students - Suryanti Suryanti; Hafni Hafsah; Ahmad Munawir; Petrus Jacob Pattiasina; Damon Wicaksi; Muta’allim Muta’allim (Austronesian: Journal of Language Science & Literature, 2026)
Writing instruction remains a major challenge in English as a Foreign Language (EFL) contexts because students tend to prioritize speaking over writing, while limited research has examined the instructional competency of Non-Native English-Speaking Teachers (NNESTs) in teaching writing. This study aims to identify the instructional competence of NNESTs in an English language institution, LPBA Nurul Jadid. This study was a qualitative study with a learning style inventory approach. The focus of this study was on the components of NNESTS competencies in institutional units and NNESTS experiences which was obtained through questionnaires, structured interviews, classroom observations, institutional curriculum documents, and supporting language proficiency certificates. The experiences of NNESTS are based on Kolb's learning cycle, as NNESTS were active learners who have learned English language skills and taught Writing skills. The results of this study proved that NNESTS still encountered problems in technical, managerial and conceptual competencies. Some of them were still unable to mediate the conflicting concepts found during the class and find new models, methods, and current issues around writing that they could develop for the following year. The findings also indicate that instructional competency develops through continuous experiential learning, reflection, and professional practice. Therefore, English language institutions should strengthen curriculum design and provide continuous professional development to improve NNESTs' instructional competency in writing instruction.